The syntax of multiple -que sentences in Spanish : along the left periphery - Villa-García, Julio (Issues in Hispanic and Lusophone linguistics ;, 2015)
Complementizers offer a window into the architecture of the left-periphery and further our understanding of the demarcation of the boundaries between the C(omplementizer) and T(ense) domains. Using the articulated left-periphery as a laboratory and Spanish constructions featuring more than one complementizer as a point of departure, the author delivers new insights into the syntactic positions and behavior of Spanish complementizer que along the left edge. These observations have far-reaching consequences to such fundamental linguistic concepts as the derivation of left dislocations, el.